An occupational pipe leak poisoning - Zhang, Xiangxing; Jian, Tianzi; Shi, Mengdi; Wang, Chen; Jian, Xiangdong; Li, Qilu (Frontiers in Pharmacology, 2025)
IntroductionDimethylacetamide (DMAC) is used as a solvent in the dye, leather, and acrylic manufacturing industries. However, it is associated with significant risks of liver and nerve damage. 4,4’-Diaminodiphenyl ether (4,4’-ODA) is a crucial precursor for synthesizing curing agents and dyes but can disrupt the methemoglobin reduction system, resulting in methemoglobinemia.MethodsThis paper reports an incident involving a plant pipeline leak on May 10, 2024, which primarily contained a DMAC solution and trace amounts of 4,4’-ODA. The patient’s occupational history, onset time of clinical symptoms, physical examination results, laboratory data, and treatment course were analyzed, and follow-up evaluation was performed to monitor the patient’s long-term health status.ResultsTwo patients exhibited clinical symptoms, including respiratory failure, methemoglobinemia, hemolytic anemia, and acute liver injury due to dermal and respiratory exposure. They were successfully treated and discharged. Notably, Patient 1 was diagnosed with toxic encephalopathy 16 days post-exposure, while Patient 2 developed peripheral neuropathy 58 days post-exposure.DiscussionThis study aimed to elucidate the clinical characteristics associated with this type of poisoning. Moreover, the incident calls for enhanced safety measures in industries using DMAC and 4,4’-ODA to prevent similar poisoning events.